American culture and the media reading, writing, thinking - Cassebaum, Anne (Houghton Mifflin, 1997)
[The book] is based on [the author's] belief that reading and writing skills are best taught together and in the context of high-interest subject matter. In section I, the mass media ... form a familiar and reassuring, yet rich and complex, subject for exploration and analysis. Section II, the rhetoric and brief handbook, gives advice and information for students to use as they work on their papers.... Fifty thematically unified high-interest readings in section I. -Pref.